Dispute system design : preventing, managing, and resolving conflict - Amsler, Lisa Blomgren, 1955-; Martinez, Janet K.; Smith, Stephanie E. (Stanford University Press, 2020)
"Dispute System Design walks readers through the art of successfully designing a system for preventing, managing, and resolving conflicts and legally-framed disputes. Drawing on decades of expertise as instructors and consultants, the authors show how dispute systems design can be used within all types of organizations, including business firms, nonprofit organizations, and international and transnational bodies. This book has two parts: the first teaches readers the foundations of Dispute System Design (DSD), describing bedrock concepts, and case chapters exploring DSD across a range of experiences, including public and community justice, conflict within and beyond organizations, international and comparative systems, and multi-jurisdictional and complex systems. This book is intended for anyone who is interested in the theory or practice of DSD, who uses or wants to understand mediation, arbitration, court trial, or other dispute resolution processes, or who designs or improves existing processes and systems."